Formulation and Evaluation of a Sheet Mask with Ethanol Extract of Mengkudu (Morinda citrifolia L.) as a Moisturizing Agent - Ginting, Indra; Mukhali, Hassan Basri bin; Abas, Mohd Ihsanuddin Bin; Aji, Andrey; Rachelli, Rachelli; Rudang, Singgar Ni (Jurnal Biologi Tropis, 2025)
Facial skin often faces issues such as acne, dullness, and dryness. Sheet masks are one of the cosmetic care products that can help maintain facial skin hydration. Noni leaves (Morinda citrifolia L.) contain secondary metabolite compounds such as alkaloids, tannins, saponins, and flavonoids, which can act as antioxidants. To determine whether noni leaf ethanol extract can be formulated into a sheet mask preparation and its effectiveness as a moisturiser. The research involved several steps: plant identification/determination, sample collection, extraction using the maceration method with 70% ethanol solvent, formulation of the sheet mask preparation, and evaluation, including organoleptic tests, homogeneity, pH, stability, irritation, and moisture effectiveness testing using a skin analyser. Sheet mask preparations with 5%, 7%, and 10% concentrations were found to be thick, homogeneous, with pH ranging from 4.42 to 5.72, non-irritating, stable during storage, and increased skin moisture by 78.94% for F1, 84.0% for F2, and 85.15% for F3. Noni leaf ethanol extract can be formulated into sheet mask preparations and is effective in moisturising the skin. Keywords: Noni leaf extract, sheet mask, moisture.